Performance of hydrophobic physical solvents for pre-combustion CO2 capture at a pilot scale coal gasification facility. (March 2023) - Smith, Kathryn H.; Ashkanani, Husain E.; Thompson, Robert L.; Culp, Jeffrey T.; Hong, Lei; Swanson, Mike; Stanislowski, Joshua; Shi, Wei; Morsi, Badie I.; Resnik, Kevin; Hopkinson, David P.; Siefert, Nicholas S.
Highlights: Hydrophobic physical solvents have been tested for pre-combustion CO2 capture. Lab-scale vapor liquid equilibrium data was measured for CO2, H2, N2 and CH4 . Pilot scale CO2 capture by physical solvents was assessed with coal derived syngas. Pilot plant performance data compared well to validated aspenPlus process simulations. CASSH-1, a hydrophobic solvent, had high CO2 uptake & low water uptake in pilot plant. Abstract: Here, we present the first pilot plant data for hydrophobic physical solvents for CO2 and H2 S removal from coal-derived H2 -rich syngas. Four physical solvents were tested under pre-combustion CO2 capture conditions at bench scale and pilot plant scale: one baseline hydrophilic solvent and three hydrophobic solvents. The solvents were: (1) polyethylene-glycol-dimethyl ether (PEGDME), a hydrophilic solvent analog for the commercial process Selexol, (2) tributyl- phosphate (TBP), a commercially available hydrophobic solvent, (3) polyethylene glycol-poly(dimethylsiloxane) (PEG-PDMS-3), and (4) diethyl sebacate (CASSH-1), a novel, computationally screened hydrophobic solvent developed by the National Energy Technology Laboratory (NETL). All solvents were studied under pure gas (CO2 /N2 /H2 /CH4 ) equilibrium conditions at NETL followed by pilot plant testing with syngas at the University of North Dakota Energy & Environmental Research Center (UND EERC). Long term performance of CASSH-1 and PEDGME was then assessed with results compared to process simulation predictions. Within experimental uncertainties, all solvents showed comparable CO2 absorption performance at above room temperature operation while the hydrophobic solvents had limited water uptake and low vapor pressure, which alleviates concerns related to corrosion, water absorption, and solvent loss to evaporation. These results indicate low viscosity, low vapor pressure hydrophobic solvents are a promising option for lower cost CO2 capture from high pressure syngas applications. Graphical abstract: Image, graphical abstract